ANALYSIS OF FACTORS AFFECTING OF RETURN ON ASSETS OF BANKING COMPANIES BEFORE AND DURING COVID-19 PANDEMIC - Punagi, Mirza; Mardi; Fauzi, Achmad (Transpublika Publisher, 2022)
This study seeks to discover the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Debt to Equity Ratio (DER) on ROA of IDX-listed banks before and during the covid-19 pandemic. The data collection method used is the documentation method. The population in this study are commercial banks listed on the Indonesia Stock Exchange in 2019 - 2020 with a total of 43 banks. The sample used is 37 Banks using the purposive sampling technique. The data analysis technique used is multiple linear regression analysis, basic assumption test, classical assumption test, and hypothesis testing. The results of this study indicate that CAR does not have a significant positive effect on ROA, NPL has a significant negative effect on ROA, and DER does not have an effect on ROA. There is no difference in CAR, NPL, DER to ROA before and during the covid-19 pandemic. Given the special situation that has an influence on the financial sector in the world, there are no differences in financial performance variables in Indonesia before and during the pandemic. This is due to risk mitigation and Risk Management in banking in Indonesia is good enough so that it does not have a significant impact.